The Design and Development of an Atraumatic Soft Robotic Surgical Retractor - Gavril Yong En Tan; Shaun Mahesh Buxani; Benjamin Wee Keong Ang; Chao Yu Chen; Raye Chen Hua Yeow; Hung Leng Kaan (IEEE Access)
This paper introduces a novel soft robotic surgical retractor system, designed to overcome the limitations of traditional surgical retractors through the integration of soft robotics. Unlike conventional rigid retractors, this innovative system features a dual-component design combining a 3D-printed thermoplastic polyurethane actuator with a stainless-steel splint (SSS), enabling variable stiffness for more effective and less traumatic tissue retraction. The study presents a comprehensive evaluation, including bending angle, blocked force measurements, actuation time efficiency, and a comparative analysis with traditional stainless steel Langenbeck retractors. Results demonstrate the soft robotic retractor’s superior performance, especially when utilizing the tip for retraction, indicating a significant alignment with the requirements for abdominal organ retraction. Furthermore, the system exhibited reduced deformation to retracted soft objects, suggesting a potential for minimizing tissue trauma compared to conventional retractors. The study proposes directions for enhancing retraction strength, optimizing design for improved force output, and conducting comprehensive testing to ensure clinical viability. This work lays the groundwork for future advancements in soft robotic surgical retractors, promising to revolutionize surgical retraction practices by offering enhanced safety and efficiency.